Association between C-reactive protein to albumin ratio and chronic obstructive pulmonary disease: a cross-sectional study - Ting Ao; Yingxiu Huang; Peng Zhen; Ming Hu (BMC Pulmonary Medicine)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a widespread condition that significantly endangers human health. The C-reactive protein to albumin ratio (CAR) has been utilized as an important marker for the occurrence and development of various diseases. Nevertheless, the association between CAR and COPD remains inadequately explored. This research aimed to examine the link between the CAR and COPD. Methods This cross-sectional study examined data from adult participants in the National Health and Nutrition Examination Survey between 1999 and 2010. The identification of COPD relied on data obtained directly from self-reported information. Logistic regression analysis was used to estimate the odds ratio (OR) and 95% confidence interval (CI) for the association between CAR and COPD. Additionally, subgroup and sensitivity analyses were performed to evaluate the stability of the observed relationship. Results The study comprised 24,627 participants, among whom 1,809 had COPD. After adjusting for potential confounders, CAR was found to be associated with COPD (OR 1.37; 95% CI, 1.12–1.69; P = 0.003). In the analysis comparing individuals in the lowest CAR tertile (T1) with those in the highest, the adjusted OR for COPD was 1.39 (95% CI, 1.17–1.65; P < 0.001). Validation through subgroup and sensitivity analyses further strengthened the stability and consistency of the study’s findings. Conclusion Elevated levels of the CAR were correlated with an increased risk of COPD. Clinical trial number : not applicable.